2015
DOI: 10.5114/jcb.2015.56766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BEBIG HDR 60 Co system for non-invasive image-guided breast brachytherapy

Abstract: PurposeHDR 60Co system has recently been developed and utilized for brachytherapy in many countries outside of the U.S. as an alternative to 192Ir. In addition, the AccuBoost® technique has been demonstrated to be a successful non-invasive image-guided breast brachytherapy treatment option. The goal of this project is to evaluate the possibility of utilizing the BEBIG HDR 60Co system for AccuBoost treatment. These evaluations are performed with Monte Carlo (MC) simulation technique.Material and methodsIn this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Besides the introduction of image-based dose calculation algorithms for 192 Ir, TG-43 remains the prevalent method for the clinical treatment planning dosimetry in HDR brachytherapy applications. While the equivalence of 60 Co and 192 Ir brachytherapy has been established in a number of studies in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 8 , 10 , 11 , 12 ], the relative effects of inhomogeneities and patient specific scatter conditions have not been considered. These effects were studied retrospectively in this work, through the comparison of TG-43 based dosimetry with corresponding MC results in groups of clinically equivalent plans with 60 Co and 192 Ir HDR sources for breast, esophageal, and cervical treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the introduction of image-based dose calculation algorithms for 192 Ir, TG-43 remains the prevalent method for the clinical treatment planning dosimetry in HDR brachytherapy applications. While the equivalence of 60 Co and 192 Ir brachytherapy has been established in a number of studies in the literature [ 1 , 2 , 3 , 4 , 5 , 6 , 8 , 10 , 11 , 12 ], the relative effects of inhomogeneities and patient specific scatter conditions have not been considered. These effects were studied retrospectively in this work, through the comparison of TG-43 based dosimetry with corresponding MC results in groups of clinically equivalent plans with 60 Co and 192 Ir HDR sources for breast, esophageal, and cervical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This development led to several comparative studies published in the literature. These include comparative evaluations of acute toxicity in gynecological cancer [ 1 , 2 ], and dosimetry studies ranging from single source dosimetry comparison [ 3 , 4 , 5 ] to comparisons of dose distributions in gynecological [ 4 , 5 , 6 , 7 ], prostate [ 8 ], skin [ 9 ], and breast [ 10 , 11 , 12 ] HDR brachytherapy treatments using different techniques. In a comprehensive dosimetry study, Palmer et al .…”
Section: Purposementioning
confidence: 99%
“…Lymperopoulou et al had shown that the plan quality with 169 Yb at least is equivalent to 192 Ir source irrespective of the prostate volume. It was also shown that, by modifying the applicator, the HDR 60 Co afterloading system can be a good alternative to the HDR 192 Ir, delivering similar dose distributions in breast cancer patients . Inverse optimization planning for cervical cancer using the 192 Ir, 169 Yb, and 60 Co sources with a tungsten alloy shielded direction‐modulated‐brachytherapy (DMBT) tandem applicator showed that 169 Yb source generated better plans for larger target volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The Monte Carlo N-Particle code (MCNP) version 6, 26 which has been successfully used in brachytherapy dosimetry by various investigators 4,8,10,15,19 is used in this study. The cross-sections used in these simulations were based on ENDF/B-VI.8 libraries.…”
Section: B Monte Carlo Study Of the Sourcesmentioning
confidence: 99%
See 1 more Smart Citation